Analisis Kesalahan Siswa dalam Menyelesaikan Soal Cerita Matematika Materi Pola Bilangan dengan Analisis Kesalahan Newman Ditinjau dari Inteligensi Siswa - Nyoman Arya Sejati; Baidowi Baidowi; Nilza Humaira Salsabila; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2023)
The purpose of this study was to describe the types and levels of errors made by class VIII B students of SMPN 1 Mataram when solving math word problems on number patterns based on Newman's error analysis in terms of student intelligence. The type of research used in this research is mixed methods. The strategy used in this study is the concurrent triangulation strategy. The sampling technique used purposive sampling, so that Class VIII B students were selected with a total of 36 students. Methods of data collection through intelligence tests, story tests with number patterns material, and interview tests. The researcher chose two students from each intelligence category to be the research subjects. The data analysis technique used in this research is descriptive statistics technique for quantitative data, then for qualitative data using the Miles and Huberman model. The following are the results of the study showing the types and levels of errors of students with intelligence (1) below average, (2) average, (3) above average who make errors in reading, understanding, question transformation, processing skills, and writing answers successively are (1) 15% (very low), 38% (low), 49% (moderate), 72% (high), 68% (high); (2) 6% (very low), 19% (low), 33% (low), 57% (moderate), 39% (low); (3) 10% (very low), 26% (low), 28% (low), 47% (moderate), 30% (low).